Energy utilized hybrid flowshop scheduling using Multi-Objective Tiki Taka Algorithm (MOTTA) - Siti Nurhazwani Husna, Mohd Hata; Muhammad Ammar, Nik Mu’tasim; Mohd Fadzil Faisae, Ab Rashid (IEEE, 2025)
This paper presents the Multi-Objective Tiki Taka Algorithm (MOTTA), a novel optimization technique for hybrid flow shop scheduling (HFS) problems emphasizing energy efficiency and makespan minimization. The algorithm is compared against five state-of-the-art algorithms MOGWO, MOAOS, MOGOA, MAOA, and MALO-using 12 Carlier Neron benchmark problems. Taguchi’s method is employed to fine-tune critical coefficients (c1,c2,c3 and problose) enhancing MOTTA’s performance. The proposed algorithm’s validity is further demonstrated through a case study, showcasing its applicability in real-world scenarios. Results indicate that MOTTA achieves superior performance in balancing trade-offs between energy utilization and makespan compared to other algorithms. The best scheduling result obtain for makespan is 2672 sec with energy consumption of 41837.09 kWatt−min.